Self-Medication Practices among Undergraduate University Students in Northeast Ethiopia - Zewdie S; Andargie A; Kassahun H (Dove Medical Press, 2020)
Segenet Zewdie,1 Assefa Andargie,2 Haile Kassahun1 1Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, Dessie, Ethiopia; 2Department of Epidemiology and Biostatistics, School of Public Health, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Haile Kassahun Department of PharmacyCollege of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaEmail haile.kassahun@wu.edu.etBackground: Inappropriate self-medication is a public-health problem worldwide. Major problems associated with self-medication include wastage of resources, increased resistance of pathogens, and adverse drug reactions.Objective: The aim of this study was to assess self-medication practices and associated factors among undergraduate Wollo University students in Northeast Ethiopia.Methods: A cross-sectional study was conducted among 341 undergraduate university students using a pretested and self-administered questionnaire from January to February 2019. Simple random sampling was used to select study participants. Data were collected using the self-administered questionnaire and analyzed with SPSS version 20. Multiple logistic regression was employed in data analysis, with P< 0.05 considered statistically significant.Results: The prevalence of self-medication in this study was 64.98%. Mildness of disease (57, 34.13%) and dissatisfaction with health-care services, (44, 26.34%) were the main reasons for self-medication practice. The most common types of diseases for self-medication were headache (80, 47.9%), gastrointestinal infections (74, 44.31%), and respiratory tract infections (48, 28.74%). Analgesics (94, 56.28%) and antibiotics (60, 35.9%) were the leading classes of medicine used in self-medication. Multivariate regression analysis indicated that agriculture students (AOR 0.163, 95% CI 0.049– 0.545) were 84% less likely to practice self-medication than medicine and health-science students.Conclusion: This study revealed that self-medication practices are common among study participants and significantly associated with their field of study. Awareness promotion on the risk of inappropriate self-medication for university students is highly recommended.Keywords: self-medication practices, undergraduate university students, Ethiopia